Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I need to prove that

$$(ah,bk)=(a,b)(h,k)\left( \frac{a}{(a,b)},\frac{k}{(h,k)}\right)\left( \frac{b}{(a,b)},\frac{h}{(h,k)}\right)$$

I'm most certain I need to use $$\left(\frac{a}{(a,b)},\frac{b}{(a,b)}\right)=1 $$ and $(a ,b)=1 $ and $a \mid bc $ then $a \mid c$ but I'm not sure how to build up the proof.

share|cite|improve this question
up vote 7 down vote accepted

Cancel $\rm\:(a,b)(h,k),\:$ write $\rm\: A = \dfrac{a}{(a,b)},\ B = \dfrac{b}{(a,b)},\ H = \dfrac{h}{(h,k)},\ K = \dfrac{k}{(h,k)}\:$ it becomes

$$\rm\ (AH,BK) = (A,K)(B,H)$$

$$\rm\iff \left(\frac{A}{(A,K)}\frac{H}{(B,H)},\, \frac{B}{(B,H)}\frac{K}{(A,K)}\right) = 1\phantom{\iff}$$

True since each term on the left is coprime to each term on the right, e.g. the first terms are coprime by $\rm\:(A,B) = (a/(a,b),\,b/(a,b)) = (a,b)/(a,b) = 1\:$ and the first and last terms are coprime by a similar argument (replace $\rm\:a,b\:$ by $\rm\:A,K).$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.